CLIMATE CHANGE IMPACTS ON SOIL PROPERTIES AND AGRICULTURAL PRODUCTIVITY - AMIN, HAB; AHSAN, M; NIAZ, A; GUL, R; NAWAZ, S; SHAH, SAH; ALI, S; AHMAD, F; MUNIR, A; AHMAD, HT (Biological and Clinical Sciences Research Journal, 2023)
There are significant and far-reaching implications for agriculture due to the extraordinary changes in the global climate. Temperature variations affect the structure of the soil, and changes in precipitation patterns and harsh weather lead to soil erosion and other negative effects. The agricultural sector faces various obstacles, ranging from fluctuations in crop yields under climate stress to difficulties managing water due to changing climate conditions. Integrating research, presenting local case studies, and considering potential future paths may provide a comprehensive picture of the intricate interactions between agriculture and climate change.